Million dollar maverick : forge your own path to think differently, act decisively, and succeed quickly - Weiss, Alan, 1946- (Brookline, MA : Bibliomotion, 2016)
"When it comes to how to succeed as an entrepreneur, we are besotted with advice. According to bestselling author Alan Weiss, success is a combination of opportunism, very disciplined work, luck, timing, and ignoring most advice. In other words, it means striking out on your own, original path to success. In Million Dollar Maverick, he explains that entrepreneurs don't take advice, they create value and then monetize it. They do what they love and are great at and find a way to sell it to people. They do not-contrary to "conventional wisdom"-chase money. They attract money. And most of all they think differently, act decisively-and, if talent and timing are with them, succeed quickly. Drawing on over thirty years of experience as a consultant, speaker, and global expert, Weiss shares his story and "Million Dollar Tips," not found in any of his other books, to help entrepreneurs gain influence, build confidence, and develop the critical thinking skills they need to discover the inside track to rapid success. "--
"Drawing on over thirty years of experience as a consultant, speaker, and global expert, Weiss shares his story and "Million Dollar Tips" to help entrepreneurs gain influence, build confidence, and develop the critical thinking skills they need to discover the inside track to rapid success"--
Includes bibliographical references (page [183]) and index.
Keywords: Success in business; Creative ability in business; Entrepreneurship; Strategic planning; Management